PENGUKURAN KREATIVITAS KETERAMPILAN PROSES SAINS DALAM KONTEKS ASSESSMENT FOR LEARNING - Bambang Subali (Jurnal Cakrawala Pendidikan, 2011)
Abstract: Measuring the Science Process Skill Creativity in the Context of Assessment for Learning. This study aims to measure the science process skill creativity in Biology in Senior High Schools (SHSs), in terms of the basic skills, process skills, and investigative skills and use them in the context of assessment for learning. The study used the learning continuum as the abstract continuum and the instruments of the divergent process science skills in Biology in SHSs developed by Bambang Subali in 2009. Two of the six instrument sets were modified and administered to 1095 students. The results show that in the process science skill creativity, the skill in data measurement is the most difficult skill among the basic skills while the observation skill is the easiest. The skill in making inferences is the most difficult skill among the process skills while the skill in making predictions is the easiest. The most difficult skill in the investigative skills is the skill in planning investigation, followed by those in reporting an investigation and making an investigation. Keywords: measurement instrument of creativity, process science skill, polytomus scale, PCM-1PL